Chemical composition and antioxidant activity of Chinese wild raspberry (Rubus hirsutus Thunb.). Issue 2 (March 2015) - Fu, Yu; Zhou, Xiaozhou; Chen, Shiguo; Sun, Yujing; Shen, Yan; Ye, Xingqian
Abstract: Wild berries are effective in nutrition, health and medical care. Berries of Rubus hirsutus Thunb. in different sizes, native to China, were analysed for nutrients including sugars, total acids and proteins and phytochemicals including ascorbic acid and polyphenols (total phenolics, total flavonoids and anthocyanins) as well as antioxidant activity. The contents of reducing sugar, total sugar, total solids, pH, total acids and proteins of R. Hirsutus Thunb. fruit were 6.23–9.79 g/100 g FW, 6.82–10.15 g/100 g FW, 11.75–13.25%, 3.67–3.86, 0.30–0.60 g/100 g FW and 0.016–0.030 g/100 g FW. The contents of ascorbic acids, total flavonoids, total phenolics and total anthocyanins were 16.33–23.28 mg/100 g, 68.23–192.11 mg/100 g, 108.23–269.90 mg/100 g and 12.43–16.71 mg/100 g. The anthocyanin composition was determined by HPLC-DAD and HPLC-UV-ESI-MS coupled with a chromogenic reagent (5% AlCl3 in ethanol). The anthocyanin composition of this fruit was identified as delphinidin-3-pentoside, which might be useful in authentication procedures. The contributions of total phenolics and total flavonoids to antioxidant activity were much greater than those of vitamin C and anthocyanins. Overall, the results verified that Chinese wild raspberry had high antioxidant activity and might be a new source of phytochemicals in the nutraceutical and functional food market. Highlights: The phytochemicals contents of wild berries in different sizes were compared. The main anthocyanin was identified as delphinidin-pentoside. The antioxidant capacities of wild berries in different sizes were compared. The relevance between antioxidant capacity and phytochemicals was analysed.